(3Jcejd bVGI aGS Ydi eG aj LPhI GdGbJHGSs - (3HdbGSe Hf CMeO GdRjGfis
(3ChdgG (B:s
(3CMeO ef NdbfG Ke Gbhd HYO UdGJfG Ydi GdfHi GdQShd SHMGf ef jHOd HGdMSf GdbHjM hGdehJ dGjPgH EdG HGdedjM s
(3BNQgG (B:s
(3dCf ef jCJ ef GdQaGb jfgHgG ai LedI GdCShGb s
(3GdeNWhWI YHGQI Yf efXheIs
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B172s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HNW GdeDdas
Keywords: (3GdJGQjNs